The many lives of magnetized neutron stars. Issue 6 (August 2014) - Perna, R.; Pons, J. A.; Viganò, D.; Rea, N.
Abstract The magnetic field strength at birth is arguably one of the most important properties to determine the evolutionary path of a neutron star. Objects with very high fields, collectively known as magnetars, are characterized by high X‐ray quiescent luminosities, occurrence of outbursts, and, for some of them, sporadic giant flares. While the magnetic field strength is believed to drive their collective behaviour, however, the diversity of their properties, and, especially, the observation of magnetar‐like bursts from "low‐field" pulsars, has been a theoretical puzzle. In this review, we discuss results of long‐term simulations following the coupled evolution of the X‐ray luminosity and the timing properties for a large, homogeneous sample of X‐ray emitting isolated neutron stars, accounting for a range of initial magnetic field strengths, envelope compositions, and neutron star masses. In addition, by following the evolution of magnetic stresses within the neutron star crust, we can also relate the observed magnetar phenomenology to the physical properties of neutron stars, and in particular to their age and magnetic field strength and topology. The dichotomy of "high‐B" field pulsars versus magnetars is naturally explained, and occasional outbursts from old, low B‐field neutron stars are predicted. We conclude by speculating on the fate of old magnetars, and by presenting observational diagnostics of the neutron star crustal field topology. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)